Rhynchophylline Regulates Calcium Homeostasis by Antagonizing Ryanodine Receptor 2 Phosphorylation to Improve Diabetic Cardiomyopathy - Liu, Jiao; Zhao, Yating; Zhu, Yufang; Wang, Yan; Liu, Xiaoshuang; Nie, Xiaobo; Zhao, Jing; Wang, Wei; Cheng, Jie (Frontiers in Pharmacology, 2022)
Diabetic cardiomyopathy (DCM) is a serious complication of diabetes that can lead to heart failure and death, for which there is no effective treatment. Rhynchophylline (Rhy) is the main effective component of the Chinese herbal medicine Uncaria rhynchophylla, which mainly acts on the cardiovascular and nervous systems. However, its role in protecting against DCM remains unexplored. The present study sought to reveal the mechanism of Rhy in improving type 2 diabetes mellitus (T2DM) myocardial lesions from the perspective of regulating calcium homeostasis in cardiomyocytes. We prepared a mouse model of T2DM using a high-fat diet combined with low doses of streptozotocin. The T2DM mice were given 40 mg/kg of Rhy for 8 weeks. The results showed that Rhy can attenuate cardiac pathological changes, slow down the heart rate, decrease serum cardiac enzyme levels, reduce cardiomyocyte apoptosis, enhance cardiomyocyte contractility, and raise the calcium transient amplitude in T2DM mice. Further, Rhy downregulated the phosphorylation level of ryanodine receptor 2, upregulated the phosphorylation level of phospholamban, protected mitochondrial structure and function, and increased adenosine triphosphate levels in the cardiac tissue of T2DM mice. Our results demonstrated that Rhy may protect against myocardial damage in T2DM mice and promote cardiomyocyte contraction, and its mechanism of action seems to be related to the regulation of intracellular calcium homeostasis.